Landscape Evolution and a Relict Fish Community, North Slope, Alaska - Rantala, Heidi Marie (2005)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by Heidi Marie Rantala in partial fulfillment of the requirements for the degree of Master of Science, April 2005. The North Slope of the Brooks Range in arctic Alaska has a complex glacial history, having been glaciated several times since the late Tertiary. As a result of these glaciations, a complex arrangement of glacial sediments is exposed on the tundra. It is the presence of the youngest glacial sediments, and their abundant lakes, which allows communities of fish to persist in this harsh environment. Although the importance of the lakes is known, the timing at which fish entered and become land-locked in specific lakes is not. The purpose of this study was to use paleolimnological information in an arctic lake, Fog Lake 3, to reconstruct the fish community dynamics in the lake, resulting from glacial and geomorphic processes on the landscape. Information about past conditions in the lake was inferred from biotic evidence and sediment characteristics in a lake sediment core. Grain size, lithology, and carbon chemistry were used as proxies for processes occurring in the lake and its watershed. The chironomid community structure was recreated throughout the length of the core by identification of fossil remains. The core was dated using 14C techniques to determine total age and sedimentation rates throughout the length of the core. The core was divided into two zones based on constrained incremental sum of squares cluster (CONISS) analysis of the grain size data. Although the CONISS analysis created zones, the only differences in grain size characteristics between zones were marginally significant. There was little difference in the carbon chemistry in the two zones. There appeared to be a significant decrease in the mass lost on ignition at 1000°C, but that mass is likely related to water in the mineral structure of clays and not proportion of carbonate rock. Zones in the core were also developed using the CONISS ...